How straw returning impacts microbial-interaction-network-mediated improvements in soil multifunctionality - Zhao, Haogeng; Lu, Zhanyuan; Cheng, Meijuan; Wei, Shuli; Fang, Jing; Cao, Wenqing; Shi, Huimin; Zhang, Wei; Zhang, Xiangqian; Qu, Yan; Liu, Lingyue; Zhang, Dejian; et al. (Frontiers in Microbiology, 2025)
IntroductionStraw returning is an important agricultural measure for improving soil health; however, the mechanism driving how it shapes the characteristics and multifunctionality of crop rhizosphere microbial communities in black-soil areas remains unclear.MethodsThrough a 3-year field experiment, combined with high-throughput sequencing, co-occurrence network analysis, and multi-model coupling, this study systematically analyzed the effects of different straw-returning rates (no straw returning, half-dose straw returning, and full-dose straw returning) on the characteristics and multifunctionality of crop rhizosphere soil microbial communities in typical black-soil areas.ResultsThe results showed that the half-dose straw-returning treatment significantly increased soil microbial diversity, whereas the full-dose straw-returning treatment significantly enriched bacterial groups such as o_Rokubacteriales and f_Anaerolineaceae and fungal groups such as Ophiocordyceps and Gigaspora. Soil nitrate nitrogen, organic carbon, microbial biomass nitrogen, microbial biomass phosphorus, and invertase activity were important factors affecting soil multifunctionality. Furthermore, co-occurrence network analysis indicated that the nodes, edges, and average degree of the fungal community under the half-dose straw-returning treatment significantly increased by 9.41, 15.93, and 30.13%, respectively, compared with those in the no-straw-returning treatment. There was a significant positive correlation between the complexity of the fungal network and microbial network and the soil multifunctional index. Additionally, microbial network complexity is a direct key factor that drives improvements in soil multifunctionality, and microbial diversity indirectly enhances soil multifunctionality by regulating microbial network complexity. Moreover, soil multifunctionality was significantly positively correlated with crop biomass and grain yield.DiscussionThis study elucidates the mechanism by which straw returning enhances black-soil fertility through the regulation of soil microbial networks, providing a theoretical basis and practical value for sustainable agricultural development and straw resource utilization in black-soil regions.